The efficacy and safety of apremilast in patients with psoriatic arthritis concurrent with comorbidity in clinical practice - E. Yu. Loginova; Yu. L. Korsakova; A. D. Koltakova; E. E. Gubar; P. L. Karpova; S. I. Glukhova; T. V. Korotaeva (Научно-практическая ревматология)
Objective: to evaluate the clinical efficacy and safety of the targeted synthetic disease-modifying antirheumatic drug (DMARD) apremilast (AP; Otesla®) in patients with active psoriatic arthritis (PsA) at 14 and 26 weeks after starting the treatment and to identify the place of AP in the combination therapy of patients with PsA, by taking into consideration a comorbidity.Subjects and methods. Examinations were made in 20 patients (11 women and 9 men) with active PsA who had comorbidity, lack of efficiency of or intolerance to previous therapy with synthetic DMARDs or biologic agents, and contraindications to its use. The median baseline Disease Activity in Psoriatic Arthritis (DAPSA) score was 35.6 [24.8; 55.6]; those of DAS and DAS28 were 3.8 [3.2; 5.0] and 4.4 [4.0; 5.2], respectively. AP (Otesla®) was administered in tablets with a starting dose of 10 mg/day with a daily dose escalation of 10 mg to the therapeutic dose of 60 mg/day for 26 weeks. At baseline, 14 and 26 weeks, the disease activity and efficiency of AP were evaluated using DAPSA, DAS, and DAS28, as well as minimal disease activity (MDA) criteria (tender joint count ≤1; swollen joint count ≤1; PASI ≤1 or BSA ≤3%; a patient’s assessment of pain ≤15 mm; patient’s global assessment ≤ 20 mm; Health Assessment Questionnaire (HAQ) ≤ 0.5; enthesitis ≤1). The investigators estimated the number of patients who had achieved remission (DAPSA≤4; DAS<1.6; DAS28<2.6), low activity (5≤DAPSA≤14; 1.6≤DAS<2.4; 2.6≤DAS28<3.2) or MDA (5 of the 7 criteria) during AP therapy at 26-week follow-up. The safety of therapy was evaluated, by analyzing the adverse events (AE): the frequency, severity, and time of their occurrence were studied.Results and discussion. At 26 weeks after AP therapy initiation, there was a significant decrease of all PsA activity scores as compared to the baseline ones to the following median values: DAPSA 25.9 [11.3; 35.2]; DAS 3.3 [1.8; 3.9], and DAS28 3.4 [2.3; 4.8]. The median BASDAI and ASDAS scores also significantly declined from 5.1 [2.5; 7.3] and 3.35 [2.3; 4.2] to 3.45 [2.15; 6.15] and 2.7 [1.8; 3.35], respectively. The median area of psoriatic skin lesions (body surface area (BSA)) significantly reduced from 2 [0.35; 6] to 1 [0.2; 2]. At 26 weeks after starting AP therapy, the low activity/remission according to DAPSA, DAS, and DAS28 was achieved by 20/10%, 20/15%, and 10/35% of patients, respectively. Three (15%) patients achieved MDA. Fifteen (75%) of the 20 patients completed an AP therapy course. In the period of 14 to 26 weeks, four patients dropped out of the study due to ineffective therapy and one because of a severe AE (pneumonia at 14 weeks of treatment); at 26 weeks, another patient was withdrawn due to lack of effect. At 14 weeks, ten patients had a moderate AE that did not required treatment discontinuation. The most common AE were diarrhea in 5 (25%) patients, headache in 4 (20%), nausea in 3 (15%), and insomnia in 3 (15%).Conclusion. AP is a safe and effective drug for the treatment of PsA patients with moderate and high inflammatory activity and various comorbidities that do not allow the use of conventional DMARDs.